RELATIONSHIP BETWEEN DIET PATTERNS AND STRESS WITH THE INCIDENCE OF GASTRITIS IN NUSA CENDANA UNIVERSITY STUDENTS IN 2025 - Wahyuni , Maria Magdalena Dwi; Hinga, Indriati Andolita Tedju; Naitkakin, Vinsensia Ensi Leu; Wunda, Brigita Virginia Safitri; Nang, Yohanes Kombi Ario; Wangge, Alexander Franklin; Nabunome, Meriani; Winda, Winda (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2025)
Gastritis is a digestive disorder caused by inflammation of the stomach that often occurs among students. Unhealthy lifestyles such as irregular eating patterns and high stress are the main risk factors for gastritis. Nusa Cendana University is a relevant location to conduct this survey because of the large number of students and the habit of consuming regional specialties that have the potential to trigger gastritis. This study aims to analyze the relationship between stress levels and eating patterns with the incidence of gastritis in Nusa Cendana University students. This study used a rapid survey design with a cross-sectional approach. A sample of 210 students was selected using the cluster random sampling technique using the Csurvey application. The independent variables consisted of eating patterns and stress, while the dependent variable was the incidence of gastritis. Primary data were collected through questionnaires, and secondary data were obtained from the Kupang City Health Office and Nusa Cendana University. Data analysis used the chi-square test. The results of the study were that out of 210 respondents, the majority of students who had poor eating patterns and experienced stress tended to experience gastritis. The results of the chi-square test showed a significant relationship between eating patterns and stress with the incidence of gastritis, where the p-value = 0,000. So it can be concluded that poor diet and high stress levels can increase the risk of gastritis in students at Nusa Cendana University in 2025.